Download presentation

Presentation is loading. Please wait.

Published byRichard Weaver Modified over 5 years ago

1
Warm-up Solve each equation. 1. k2 = b2 = 169 3. m2 – 196 = c = 36 5. 6w2 – 24 = p2 = 4 k = ±9 b = ±13 m = ±14 c = 0 w = ±2

2
**Factoring to Solve Quadratic Equations**

Section 9.5 Factoring to Solve Quadratic Equations Objective: I will solve quadratic equations by factoring. Standards: 14.0, 23.0, 25.1

3
**Zero Product Property:**

If the product of two or more binomials equals 0, then each binomial equals 0. (x + 3)(x + 2) = 0 (x + 3) = 0 and (x + 2) = 0

4
Solve each equation. (x + 4)(x – 8) = 0 (x + 4) = 0 (x – 8) = 0 x + 4 = 0 x – 8 = 0 -4 +8 x = -4 x = 8

5
Solve each equation. (5x + 4)(2x – 5) = 0 (5x + 4) = 0 (2x – 5) = 0 5x + 4 = 0 2x – 5 = 0 +5 +5 5x = -4 2x = 5

6
Solve each equation. y(y – 1) = 0 y = 0 (y – 1) = 0 y – 1 = 0 +1 y = 1

7
Solving a quadratic: If there are three terms: Factor using the X or the box method. Use the zero product property to solve each binomial. Check your answer.

8
**12 3 4 7 Solve by factoring: x2 + 7x + 12 = 0 Factors of 12: 1 and 12**

9
**-28 4 -7 -3 Solve by factoring: b2 – 3b – 28 = 0 Factors of -28:**

1 and -28 4 -7 2 and -14 -3 4 and -7 (b + 4)(b – 7) = 0 b + 4 = 0 b – 7 = 0 b = -4 b = 7

10
Solve by factoring: 3a2 + 4a – 4 = 0 Multiply 3 & -4 3a 3a2 6a -12 -2 -2a -4 -1 and 12 11 -2 and 6 4 a 2 -3 and 4 1 (3a – 2)(a + 2) = 0 3a – 2 = 0 a + 2 = 0 3a = 2 a = -2

11
Solve by factoring: 3x2 + 16x + 5 = 0 Multiply 3 & 5 x 3x2 1x 15 5 15x 5 1 and 15 16 3 and 5 8 3x 1 (3x + 1)(x + 5) = 0 3x + 1 = 0 x + 5 = 0 3x = -1 x = -5

Similar presentations

Presentation is loading. Please wait....

OK

Copyright © Cengage Learning. All rights reserved.

Copyright © Cengage Learning. All rights reserved.

© 2018 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google